2001
DOI: 10.4049/jimmunol.167.4.2298
|View full text |Cite
|
Sign up to set email alerts
|

Sensitized Mast Cells Migrate Toward the Agen: A Response Regulated by p38 Mitogen-Activated Protein Kinase and Rho-Associated Coiled-Coil-Forming Protein Kinase

Abstract: Although mast cells accumulate within the mucosal epithelial layer of patients with allergic rhinitis and bronchial asthma, the responsible chemotactic factors are undefined. We investigated whether mast cells sensitized with Ag-specific IgE migrate toward the Ag. MC/9 mast cells sensitized with anti-DNP IgE migrated toward DNP-conjugated human serum albumin. This migration was directional, and the degree was stronger than that induced by stem cell factor. IL-3 and stem cell factor-dependent cultured mast cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 51 publications
2
38
1
Order By: Relevance
“…It has been reported that both IgE and IgEantigen induce mast-cell migration (Ishizuka et al, 2001;Jung et al, 2009;Kitaura et al, 2005), whereas another report noted that these responses might merely reflect chemokinesis or the autocrineparacrine action of chemotactic factors that are released from the activated mast cells (Kitaura et al, 2005;Taub et al, 1995). In the current study, we opted not to use fibronectin-coated membranes as used previously (Kitaura et al, 2005) to avoid the potential activation of integrin receptors that might augment chemotactic responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that both IgE and IgEantigen induce mast-cell migration (Ishizuka et al, 2001;Jung et al, 2009;Kitaura et al, 2005), whereas another report noted that these responses might merely reflect chemokinesis or the autocrineparacrine action of chemotactic factors that are released from the activated mast cells (Kitaura et al, 2005;Taub et al, 1995). In the current study, we opted not to use fibronectin-coated membranes as used previously (Kitaura et al, 2005) to avoid the potential activation of integrin receptors that might augment chemotactic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Others include several agonists of G-protein-coupled receptors (GPCRs), such as prostaglandin E 2 (PGE 2 ), which positively regulates mast-cell responses through the EP3 receptor (Weller et al, 2007). There is also evidence to suggest that IgEsensitized mast cells migrate toward antigen, potentially through the release of chemoattractants from mast cells themselves (Ishizuka et al, 2001;Kitaura et al, 2005). This evokes a potential contributory role for the high-affinity receptor for IgE (FcRI) in mast-cell homing, in addition to its role in release of the mast-cell mediator.…”
Section: Introductionmentioning
confidence: 99%
“…These Rho-like G-proteins are known principally for their pivotal role in regulating the actin cytoskeleton in cell migration (Burridge and Wennerberg, 2004). PI3K has been thought to be a key molecule in the activation of cell migration through Rac signaling (Chandrasekar et al, 2003;van Leeuwen et al, 2003 Kawauchi et al, 2003) and p38MAPK (Rousseau et al, 1997;Cara et al, 2001;Ishizuka et al, 2001;Kimura et al, 2003;Pichon et al, 2004), have also been reported to be involved in cell migration. Consistent with these reports, our results indicate that activation of PI3K is required for the induction of glioma cell migration as well as for the activation of p38MAPK and JNK in response to LPA.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate carcinoma cells (Edlund et al, 2002), Cdc42 as well as RhoA could participate in not only transforming growth factor-binduced formation of stress fibers but also in membrane ruffling. It has been shown that p38MAPK, MAPKKAPKs and hsp25/27 might be involved in polymerization of actin (Ishizuka et al, 2001). Recent finding has also shown that JNK phosphorylates paxillin, and suggested that phosphorylation of actin-associated adaptor proteins for focal adhesion is a possible mechanism through which JNK affects the organization of actin cytoskeleton and the migration of epithelial cells .…”
Section: Discussionmentioning
confidence: 99%
“…Much is known that cross-linking of IgE bound to Fc⑀RI by specific Ag mediates rapid release of biologically active chemical mediators and production of proinflammatory cytokines. Recently, IgE binding to the mast cell surface has been reconfirmed to mediating directional migration toward IgE-specific Ag (20,21). Moreover, monomeric IgE up-regulates Fc⑀RI expression and induces survival and cytokine production of mast cells (22)(23)(24).…”
mentioning
confidence: 99%